Barghouth, Abdul Aziz. “Divine Universal Laws (Sunnan Ilāhiyyah) in Early Islamic Thought,” Year 11, Issue 44 (Spring 1427 AH/ 2006 CE), Pp. 59-90. - برغوث عبد العزيز (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2006)
Abdul Aziz Barghouth’s article addresses two problematic issues. The first of these is the view that efforts of early Islamic thought did not establish an independent science to study Divine universal laws (Sunnan Ilāhiyyah) as it did with Shariʿah and the intellectual sciences. The second of these, which is a consequence of the first, finds that the presence of a fiqh of Divine universal laws in the efforts of later scholars was meager, suggesting the weakness of this science in the life of the Ummah. The article addresses the following points from this perspective: the theoretical framework to study the issue of Sunnan Ilāhiyyah in early Islamic thought; the presence of Sunnanī consciousness and a perspective inferred from the efforts of later scholars; and models of Sunnanī consciousness and Sunnanī culture in the efforts of later scholars.